Access and equity: what do we know about government primary school students' remote learning experience during school closures in Bangladesh? - Manjuma Akhtar Mousumi (Emerald Publishing, 2023)
Purpose - The study explores government primary school students' remote learning experience during school closures due to COVID-19. Design/methodology/approach - A qualitative approach and semi-structured interviews were employed for data collection. The study used a snowball sampling procedure to select 24 participants. Findings - This study shows that students experienced setbacks in learning due to not having access to resources. Besides, online classes were expensive as they were not able to buy devices, internet package and other resources to participate in the remote classes. Since many students were unable to access digital media and get parental and teacher support for education, students' engagement in learning was very low. Moreover, the paucity of learning due to school closures has lowered students' motivation for learning. The study also contributed to understanding children's emotional attachment with the schools and how the closure affected their well-being. The results indicate that the students, teachers and parents did not have a positive experience with remote teaching-learning and the modalities did not contribute to continuing with meaningful learning. Originality/value - The remote learning experience shared in this study can be used to inform policymakers, educators and stakeholders exploring remote learning solutions in low-resource contexts. This study contributes to understanding the skills and competencies teachers require to support children's learning during any crisis.